Pengaruh Kepribadian, Self Eficacy dan Locus of Control Terhadap Kinerja Karyawan Bagian Akuntansi Pada Koperasi Simpan Pinjam di Kota Denpasar Dengan Budaya Catur Purusa Artha Sebagai Variabel Moderasi - Gede Hendra Eka Saputra; Anantawikrama Tungga Atmadja; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2023)
Abstract Cooperatives have an important role in building the economy of a region, high inactive cooperatives indicate that cooperative performance is still low. This is what underlies the research with the aim of knowing the influence of personality, self-efficacy and locus of control on performance moderated by the Purusha Arta Catur Culture. This type of research is included in quantitative research with a causal approach or cause and effect. The research sample was employees of the accounting department at a savings and loan cooperative in Denpasar City. The research instrument used a questionnaire. The data analysis method in this study uses Structural Equation Modeling Partial Least Square (SEM PLS). The results show that personality, self-efficacy and locus of control have a positive effect on the performance of accounting employees but the culture of Catur Purusa Artha has a positive but not significant effect, meaning that Catur Purusa Artha is not able to stand alone in influencing the performance of subsequent employees with the presence of Catur Purusa Artha (CPA). able to strengthen the influence of personality, self-efficacy and locus of control on performance.. Keywords: personality, self efficacy and locus of control, catur purusa artha & performance